RASIONALITAS KAN'AN DALAM MENOLAK DAKWAH NABI NUH AS PERSPEKTIF AL-QUR’AN - Ismail, Hidayatullah; Prasetyo, Toto; Novendri_S, Mochammad; Yahya_Ma’ali, Dasman (Khulasah : Islamic Studies Journal, 2024)
This study aims to explore the rationality of Kan'an in the story of Prophet Noah (AS) from the perspective of the Qur'an. The story of Prophet Noah is one of the significant narratives in the Qur'an with profound relevance in understanding Islam. This research focuses on the attitude of Kan'an, one of Prophet Noah's sons, who refused to follow his father's command to board the ark that would save them from the forthcoming great flood as a punishment for the disbelieving people. The research methodology involves an in-depth textual analysis of the Qur'an using the thematic exegesis approach (tafsir maudhu’i). The analysis results indicate that Kan'an's attitude in the story can be interpreted rationally from certain perspectives. Factors such as cultural identity, fear of uncertainty, and considerations of resources and safety form the basis for his decision. This study significantly contributes to our understanding of the complexity of narratives in the Qur'an and their relevance to contemporary cultural and social contexts. Furthermore, this research emphasizes the importance of a hermeneutic approach that is sensitive to cultural contexts in interpreting religious texts.